Let Z ∗ be the set of non-negative integers.
Given that λ 0 , λ 1 , λ 2 , … are real numbers that satisfy, for all n ∈ Z ∗ ,
a + b + c = n ∑ λ a λ b λ c = 1
where the sum is taken over all a , b , c ∈ Z ∗ such that a + b + c = n . (In particular, λ 0 = 1 .)
It turns out that for all n ∈ Z ∗ there is a nice closed form for λ n . Using such a form, determine ⌊ 1 0 0 0 λ 2 0 1 6 ⌋ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The change I made due to Ivan's comment also fixes the issue in the note.
This solution was made when question said λ n = ( − 1 ) n ( n p / q ) for all n , and you were finding p + q . The new answer can simply be found by evaluating ⌊ 1 0 0 0 ∣ ( 2 0 1 6 − 1 / 3 ) ∣ ⌋ .
Using n = 0 , we get λ 0 3 = 1 or λ 0 = 1 .
Using n = 1 , we get 3 λ 0 2 λ 1 = 1 or λ 1 = 3 1 .
Matching this to the given form, we have:
λ 1 3 1 q p = ( − 1 ) 1 ( 1 p / q ) = − q p = 3 − 1
Thus p = − 1 , q = 3 , and p + q = 2 .
Tip: Instead of asking for the general form (and thus can be abused like above), ask for some specific value like λ 2 0 1 5 or something.
EDIT: This solution was written when the question said λ n = ( − 1 ) n ( n p / q ) for all n , and finding p + q .
I have changed the question to ask for ⌊ 1 0 0 0 λ 2 0 1 6 ⌋ instead, which lets the answer stay at two. Thank you for letting me know about this, it completely slipped my mind when writing the problem.
Problem Loading...
Note Loading...
Set Loading...
As generating functions, ( λ 0 + λ 1 x + λ 2 x 2 + ⋯ ) 3 = 1 + x + x 2 + ⋯ = ( 1 − x ) − 1 , so λ 0 + λ 1 x + λ 2 x 2 + ⋯ = ( 1 − x ) − 3 1 . Taking the coefficient of x n in both sides, we get λ n = ( − 1 ) n ( n − 3 1 ) .
Note: As stated, the problem is ambiguous, since − 3 1 can be written as 3 − 1 or − 3 1 .